Pendampingan Orang Tua Pengantar Siswa RA dalam Pembuatan Alat Permainan Edukatif (APE) di Kecamatan Trowulan dan Kecamatan Sooko Kabupaten Mojokerto - Gesa Kharisma Putri; Solihati Solihati; Haya Haya (Program Studi PGRA, 2017)
The development of Early Childhood Education throughout Indonesia welcomed by the public, including in Mojokerto regency, in particular districts and sub-districts Trowulan Sooko. Parents have the awareness of the importance of early childhood education for 0-6 years). Children aged 3-6 years have a different development, there are children who are self-biased some are not. Children who have not been independently still need the help of parents in various activities including when children go to school. Some parents choose to stay in school to wait for her son and daughter following study from beginning to end because their children have not been left bias, so parents have to stand by in school. However, the presence of parents introductory students in schools that the majority of the mothers did not show productive activities. During his sons and daughters to follow the lesson in class until the end of the lesson, not a lot of activities undertaken in addition to chatting or exchanging stories / experiences. Departing from these problems, in the context of community service, we have done a mentoring program for parents of students introductory RA in manufacturing Games Educational Tool (APE). Parents are given insight into the Games Educational Tool (APE) with the aim that they can take advantage of free time while waiting for their child in the class and their activities have been more helpful. Besides being able to make the activity more productive, APE result they make can be used for mutual learning of their children at home in particular, and can help the school to improve the collection of APE in general.